2018
DOI: 10.1124/dmd.118.081596
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Human Hepatocyte Low Intrinsic Clearance Assay for Use in Drug Discovery

Abstract: Progression of new chemical entities is a multiparametric process involving a balance of potency; absorption, distribution, metabolism, and excretion; and safety properties. To accurately predict human pharmacokinetics and estimate human efficacious dose, the use of in vitro measures of clearance is often essential. Low metabolic clearance is often targeted to facilitate in vivo exposure and achieve appropriate half-life. Suspension primary human hepatocytes (PHHs) have been successfully used in predictions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In a challenge to long-term co-culture models, Lancett et al recently showed data indicating that new culture supplements and Matrigel overlay may be employed to sufficiently slow the decay of enzyme activities in monoculture-plated cells to enable multiple-day usage. 39 They reported the Matrigel overlay to enable robust intrinsic clearance predictions over a duration of 30 h, with high gene expression levels for CYP, UGT, and nuclear receptors maintained over this time course. The uncomplicated nature and high cell density (350,000 hepatocytes per well in a 24-well plate) of this system could enable measurement of in vitro intrinsic clearance for highly metabolically stable compounds at lower cost than using the sophisticated co-cultures.…”
Section: Extrapolationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a challenge to long-term co-culture models, Lancett et al recently showed data indicating that new culture supplements and Matrigel overlay may be employed to sufficiently slow the decay of enzyme activities in monoculture-plated cells to enable multiple-day usage. 39 They reported the Matrigel overlay to enable robust intrinsic clearance predictions over a duration of 30 h, with high gene expression levels for CYP, UGT, and nuclear receptors maintained over this time course. The uncomplicated nature and high cell density (350,000 hepatocytes per well in a 24-well plate) of this system could enable measurement of in vitro intrinsic clearance for highly metabolically stable compounds at lower cost than using the sophisticated co-cultures.…”
Section: Extrapolationmentioning
confidence: 99%
“…The uncomplicated nature and high cell density (350,000 hepatocytes per well in a 24-well plate) of this system could enable measurement of in vitro intrinsic clearance for highly metabolically stable compounds at lower cost than using the sophisticated co-cultures. 39 Alternative approaches, such as spheroids or more MPSs, are discussed later.…”
Section: Extrapolationmentioning
confidence: 99%
“…One possible mechanism behind the underprediction could be technical issues. For instance, inappropriate concentrations of assay reactants and of substrates can result in the underestimation of metabolic rates (Wood et al 2017; Lancett et al 2018). Similarly, the use of solvents for hydrophobic chemicals can influence the in vitro clearance rate (Escher et al 2011; Lee et al 2014).…”
Section: Resultsmentioning
confidence: 99%